Oriented‐Etched Graphite for Low‐Temperature Lithium‐Ion Batteries. Issue 4 (7th February 2023) - Xu, Jiang; Wang, Xuanding; Hu, Bingqing; Ding, Jianning; Zhang, Zhongqiang; Ge, Shanhai
Abstract: As an environmentally friendly energy storage media, lithium‐ion batteries have been extensively used and investigated. However, fast‐charging and low‐temperature tolerance are still huge challenges for the graphite‐based batteries. To alleviate the poor rate performance caused by long diffusion path and the risk of lithium dendrite growth at high rate or low temperature charging, graphite with penetrated macropores is fabricated here, combined with ether‐based electrolyte with low solvation energy, the smooth migration of Li + /Li at the electrolyte‐electrode interface and interior of the graphite is ensured. The product graphite exhibits excellent rate and low‐temperature performance, evidenced by 352.9 mAh g −1 capacity delivered at 2 C‐rate and −30 °C. In addition, benefited from the intact preservation of the pristine graphite structure, it exhibits ∼85 % initial charge‐discharge efficiency and long cycle life (∼94.2 % capacity retention after 500 cycles). This synergic strategy makes the product graphite very efficient in the fast charging/discharging and low temperature occasions. Abstract : Macropores for lithium transportation : An electrode‐electrolyte strategy combining oriented‐etched macroporous graphite with 1, 3‐dioxolane‐based electrolyte is designed to improve the migration of Li + /Li at the electrolyte‐electrode interface and interior of the graphite. Lithium‐ion battery in this synergistic system shows excellent cycling stability and outstanding performance under high rate and low‐temperature.